Resin composition
By using a combination of a liquid epoxy resin containing multiple epoxy groups and methacrylic anhydride, the problem in the prior art is solved that it is difficult to achieve both low viscosity and high glass transition temperature, and a resin composition and a cured product with excellent heat resistance are realized.
Patent Information
- Application Number
- CN202380054987.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-06-19
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to achieve both low viscosity resin compositions and cured products with high glass transition temperatures, especially in applications where excellent heat resistance is required.
By using a resin composition containing (A-1) an epoxy resin containing more than 2 epoxy groups in one molecule and (B) methacrylic anhydride in liquid form at 25°C, the viscosity before curing can be reduced and the glass transition temperature after curing can be increased.
It achieves both low viscosity and high glass transition temperature, and provides cured substances with excellent heat resistance while maintaining good fluidity and dielectric properties.
Smart Images

Figure CN119585335A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and also to a cured product of the resin composition, a semiconductor chip package and a semiconductor device comprising the cured product. Background Art
[0002] Low-viscosity resin compositions containing epoxy resins are in high demand for applications in organic-inorganic composite materials that require high filling of inorganic fillers and high permeability to fiber materials (e.g., glass fibers and carbon fibers). Therefore, various studies have been conducted on resin compositions that can reduce viscosity (Patent Documents 1 and 2).
[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2010-70605 Patent document 2: Japanese Patent No. 6340762. Summary of the invention
[0004] Technical problem to be solved by the invention From the viewpoint of obtaining a cured product with low dielectric loss tangent, an inorganic filler is sometimes added to the resin composition. Generally speaking, there is a tendency for fluidity to decrease as the content of the inorganic filler in the resin composition increases, but when a low-viscosity resin composition is used, the decrease in fluidity can be relatively suppressed.
[0005] On the other hand, in applications requiring heat resistance, it is desirable that the glass transition temperature of the cured product be high. However, generally speaking, a cured product obtained by curing a resin composition capable of lowering viscosity tends to have a low glass transition temperature.
[0006] Against the background of such technological trends and technical knowledge, there is a demand for a resin composition that can provide a cured product having excellent heat resistance and can be reduced in viscosity.
[0007] The present invention is proposed in view of the above-mentioned problems, and its purpose is to provide: a resin composition that can obtain a cured product with a high glass transition temperature and can be reduced in viscosity; a cured product of the resin composition; and a semiconductor chip package and a semiconductor device including the cured product.
[0008] Technical solutions adopted to solve technical problems The present inventors have conducted earnest research to solve the above-mentioned problems. As a result, the present inventors have found that a combination of (A) epoxy resin including (A-1) an epoxy resin containing two or more epoxy groups in one molecule and being liquid at 25°C, and (B) a resin composition of methacrylic anhydride can solve the above-mentioned problems, thereby completing the present invention. In addition, the present inventors have found that if the above-mentioned resin composition is used, good fluidity can be obtained even when an inorganic filler is added based on the viewpoint of obtaining a cured product with a low dielectric loss tangent, and a large amount of inorganic fillers and other components can be added to achieve a cured product with particularly excellent dielectric properties. The present invention originates from the above-mentioned insights.
[0009] That is, the present invention includes the following contents. [1] A resin composition which is a liquid resin composition at 25°C, The resin composition comprises (A) an epoxy resin and (B) methacrylic anhydride, (A) The epoxy resin includes (A-1) an epoxy resin having two or more epoxy groups in one molecule and being liquid at 25°C. [2] The resin composition according to [1], wherein the amount of the component (A-1) is 10% by mass to 100% by mass relative to 100% by mass of the component (A). [3] The resin composition according to [1] or [2], wherein the viscosity of the component (A-1) at 25°C is 100,000 mPa·s or less. [4] The resin composition according to any one of [1] to [3], wherein the viscosity of the component (A) at 25°C is 100,000 mPa·s or less. [5] The resin composition according to any one of [1] to [4], wherein the mass ratio of component (A) / component (B) is 20 / 80 to 80 / 20. [6] The resin composition according to any one of [1] to [5], further comprising (C) a compound having 1 to 3 ethylenically unsaturated bonds in addition to the component (B). [7] The resin composition according to [6], wherein the viscosity of the component (C) at 25°C is 30 mPa·s or less. [8] The resin composition according to [6] or [7], wherein the mass ratio of (component (A) + component (B)) / component (C) is 30 / 70 to 95 / 5. [9] The resin composition according to any one of [1] to [8], further comprising (D) an epoxy polymerization accelerator.
[10] The resin composition according to any one of [1] to [9], further comprising (E) a radical polymerization initiator.
[11] The resin composition according to any one of [1] to
[10] , further comprising (F) an inorganic filler.
[12] The resin composition according to
[11] , wherein the component (F) is silica.
[13] The resin composition according to
[11] or
[12] , wherein the amount of the component (F) is 40% to 95% by mass relative to 100% by mass of the non-volatile matter in the resin composition.
[14] The resin composition according to any one of
[11] to
[13] , wherein the viscosity of the resin composition at 25°C is 1000 mPa·s or less, and the viscosity of the resin component of the resin composition at 25°C is 30 mPa·s or less.
[15] The resin composition according to any one of [1] to
[14] , which contains no organic solvent or contains less than 3% by mass of an organic solvent.
[16] The resin composition according to any one of [1] to
[15] , wherein when the resin composition is cured at 100° C. for 5 hours to obtain a cured product, The cured product has a glass transition temperature Tg of 220°C or less. The average linear thermal expansion coefficient CTEα1 of the cured product in the first measurement range of 40°C to 60°C is less than 50 ppm / °C, and the average linear thermal expansion coefficient CTEα2 of the cured product in the second measurement range of Tg+40°C to 260°C is less than 100 ppm / °C.
[17] The resin composition according to any one of [1] to
[16] , wherein when the resin composition is cured at 100°C for 5 hours to obtain a cured product, the cured product has a glass transition temperature Tg of 150°C or higher.
[18] The resin composition according to any one of [6] to [8], wherein the component (C) contains glycidyl methacrylate or 4-hydroxybutyl acrylate glycidyl ether.
[19] The resin composition according to any one of [1] to
[18] , which is an underfill material.
[20] A semiconductor chip package comprising a cured product of the resin composition according to any one of [1] to
[19] .
[21] The semiconductor chip package according to
[20] , comprising: a substrate, a semiconductor chip disposed on the substrate with a gap left thereon, and the cured product filling the gap.
[22] A semiconductor device comprising the semiconductor chip package described in
[20] or
[21] .
[23] A cured product of the resin composition according to any one of [1] to
[19] .
[0010] Effects of the Invention According to the present invention, it is possible to provide a low-viscosity resin composition capable of obtaining a cured product having a high glass transition temperature, a cured product of the resin composition, and a semiconductor chip package and a semiconductor device including the cured product.
[0011] Brief description of the attached figure Figure 1 It is a cross-sectional view schematically showing a semiconductor chip package according to a first example of the present invention. Figure 2 It is a cross-sectional view schematically showing a semiconductor chip package according to a second example of the present invention. Figure 3 FIG. 1 is a cross-sectional view schematically showing a semiconductor chip package according to a third example of the present invention. Figure 4 FIG. 4 is a cross-sectional view schematically showing a semiconductor chip package according to a fourth example of the present invention. Figure 5 FIG. 5 is a cross-sectional view schematically showing a semiconductor chip package according to a fifth example of the present invention. Figure 6 FIG. 1 is a cross-sectional view schematically showing a semiconductor chip package according to a sixth example of the present invention. DETAILED DESCRIPTION
[0012] Hereinafter, the present invention will be described in detail with reference to the embodiments and examples. However, the present invention is not limited to the embodiments and examples given below, and can be implemented with arbitrary modifications within the scope of the claims and their equivalents.
[0013] In the following description, unless otherwise specified, the term "(meth)acrylic acid" includes acrylic acid and methacrylic acid. In addition, unless otherwise specified, the term "(meth)acrylate" includes acrylate and methacrylate. In addition, unless otherwise specified, the term "(meth)acryloyl" includes acryloyl and methacryloyl.
[0014] [Overview of resin composition] The resin composition involved in one embodiment of the present invention is liquid at 25°C. In addition, the resin composition involved in this embodiment contains (A) epoxy resin and (B) methacrylic anhydride. And, (A) epoxy resin contains (A-1) epoxy resin containing two or more epoxy groups in one molecule and being liquid at 25°C. In the following description, "(A-1) epoxy resin containing two or more epoxy groups in one molecule and being liquid at 25°C" is sometimes referred to as "(A-1) multifunctional liquid epoxy resin".
[0015] The resin composition involved in the present embodiment can have a lower viscosity. Specifically, (A-1) multifunctional liquid epoxy resin is liquid at 25°C, and (B) methacrylic anhydride is a low-viscosity liquid compound, so the resin composition containing these components can easily achieve a low-viscosity liquid state. In addition, generally speaking, the previous cured product obtained by combining (A-1) multifunctional liquid epoxy resin with an epoxy curing agent other than methacrylic anhydride has a tendency to have a low glass transition temperature. Relatively speaking, the cured product obtained by combining (A-1) multifunctional liquid epoxy resin with (B) methacrylic anhydride as in the present embodiment can reduce the viscosity before curing and can have a higher glass transition temperature Tg. The effect of reducing the viscosity before curing and increasing the glass transition temperature Tg after curing is an effect that cannot be obtained when using an epoxy curing agent with a chemical structure similar to methacrylic anhydride such as acrylic anhydride, and is therefore a special effect obtained by combining (A-1) multifunctional liquid epoxy resin with (B) methacrylic anhydride. Furthermore, when the resin composition according to the present embodiment is used as described above, a cured product having a high glass transition temperature can be obtained, so that both low viscosity and high glass transition temperature can be achieved at the same time.
[0016] Furthermore, when the resin composition according to the present embodiment is used, a cured product with low thermal expansion can generally be obtained. Furthermore, the resin composition according to the present embodiment is preferably a composition with low viscosity increase (thickening) over time.
[0017] [(A) Epoxy resin] The resin composition according to the present embodiment includes (A) an epoxy resin as the component (A). The epoxy resin (A) may be a curable resin containing an epoxy group. The epoxy resin (A) includes (A-1) a multifunctional liquid epoxy resin.
[0018] The multifunctional liquid epoxy resin (A-1) contains two or more epoxy groups in one molecule. The number of epoxy groups contained in one molecule of the multifunctional liquid epoxy resin (A-1) is usually two or more, preferably 10 or less, more preferably 5 or less, and further preferably 4 or less. If the multifunctional liquid epoxy resin (A-1) containing two or more epoxy groups in one molecule is used, a complex cross-linked network can be formed during curing, so that a cured product with excellent mechanical strength and thermal stability can be obtained, for example, a cured product with small thermal expansion can be obtained.
[0019] (A-1) The multifunctional liquid epoxy resin is in liquid form at 25°C. In the present specification, (A-1) the multifunctional liquid epoxy resin is in "liquid form" means that (A-1) the multifunctional liquid epoxy resin has fluidity. Specifically, the viscosity of (A-1) the multifunctional liquid epoxy resin at 25°C is preferably in the range of 100,000 mPa·s or less, more preferably 70,000 mPa·s or less, and further preferably 50,000 mPa·s or less. The lower limit of the viscosity of (A-1) the multifunctional liquid epoxy resin at 25°C may be, for example, 1 mPa·s or more, 5 mPa·s or more, 10 mPa·s or more, etc. The viscosity can be measured using a vibration viscometer (for example, "VM-10A-L" manufactured by Sekonic Co., Ltd.). The specific method for measuring the viscosity can be the method described in the examples.
[0020] In particular, from the viewpoint of obtaining a cured product having excellent heat resistance, the polyfunctional liquid epoxy resin (A-1) preferably contains an aromatic structure in the molecule. The aromatic structure refers to a chemical structure generally defined as an aromatic structure, and also includes polycyclic aromatics and aromatic heterocycles.
[0021] Examples of the (A-1) multifunctional liquid epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol AF epoxy resin, hydrogenated bisphenol A epoxy resin, naphthalene epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, phenol novolac epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane epoxy resin, and cyclohexanedimethanol epoxy resin. Among them, bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene epoxy resin, and glycidyl amine epoxy resin are preferred.
[0022] Specific examples of the (A-1) multifunctional liquid epoxy resin include "HP-4032", "HP-4032D", and "HP-4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation, "828US", "828EL", "jER828EL", and "825" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation, "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation, "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "630", "630LSD", "604", and "JER-60" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation, 4" (glycidylamine type epoxy resin), "ED-523T" (GLYCIROL type epoxy resin) manufactured by ADEKA Corporation, "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation, "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation, "ZX-1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd., "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Co., Ltd., "CELLOXIDE 2021P" (alicyclic epoxy resin with an ester skeleton), "ZX1658" and "ZX1658GS" (1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd., "YX8000" (hydrogenated bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation, and "KF-101" (epoxy-modified silicone resin) manufactured by Shin-Etsu Chemical Co., Ltd.
[0023] (A-1) The multifunctional liquid epoxy resin may be used alone or in combination of two or more.
[0024] The epoxy equivalent of the (A-1) multifunctional liquid epoxy resin is preferably in the range of 50 g / eq. to 300 g / eq. The upper limit of the range is preferably 250 g / eq. or less, more preferably 240 g / eq. or less, more preferably 220 g / eq. or less, more preferably 200 g / eq. or less, and more preferably 180 g / eq. or less. The epoxy equivalent represents the mass of the resin per 1 equivalent of epoxy group. The epoxy equivalent can be measured in accordance with JIS K7236.
[0025] The weight average molecular weight (Mw) of the (A-1) polyfunctional liquid epoxy resin is preferably in the range of 100 to 5000, more preferably 250 to 3000, further preferably 400 to 1500. The weight average molecular weight of the resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0026] The amount of the multifunctional liquid epoxy resin (A-1) is preferably 10% by mass or more, more preferably 30% by mass or more, and further preferably 50% by mass or more, and is usually 100% by mass or less, relative to 100% by mass of the epoxy resin (A). When the amount of the multifunctional liquid epoxy resin (A-1) is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can usually be effectively reduced.
[0027] About the scope of the amount of (A-1) multifunctional liquid epoxy resin, relative to the non-volatile component 100 mass % in the resin combination, preferably more than 1 mass %, more preferably more than 2 mass %, further more preferably more than 3 mass %, preferably less than 70 mass %, more preferably less than 65 mass %, particularly preferably less than 60 mass %. The non-volatile component in the resin combination represents the component other than the organic solvent (I) in the resin combination. When the amount of (A-1) multifunctional liquid epoxy resin is within the range, the reduction of the viscosity of the resin combination and the increase of the glass transition temperature of the cured product can be achieved at a high level, and then the thermal expansion of the cured product can be effectively reduced usually.
[0028] About the scope of the amount of (A-1) multifunctional liquid epoxy resin, relative to 100 mass % of the resin component in the resin composition, preferably more than 1 mass %, more preferably more than 5 mass %, further more preferably more than 10 mass %, preferably less than 70 mass %, more preferably less than 65 mass %, particularly preferably less than 60 mass %. The resin component in the resin composition represents the component other than (F) inorganic filler in the non-volatile component in the resin composition. When the amount of (A-1) multifunctional liquid epoxy resin is within the range, the reduction of the viscosity of the resin composition and the increase of the glass transition temperature of the cured product can be achieved at a high level, and then the thermal expansion of the cured product can be usually effectively reduced.
[0029] (A) The epoxy resin may include (A-2) any epoxy resin other than (A-1) the multifunctional liquid epoxy resin. Examples of (A-2) any epoxy resin include epoxy resins containing one epoxy group in one molecule and epoxy resins that are solid at 25°C.
[0030] Examples of the arbitrary epoxy resin (A-2) include biphenylol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, naphthol novolac-type epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, naphthol aralkyl-type epoxy resins, biphenyl-type epoxy resins, naphthyl ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, phenol aralkyl-type epoxy resins, tetraphenylethane-type epoxy resins, and phenolphthalimidine-type epoxy resins.
[0031] (A-2) Any epoxy resin may be used alone or in combination of two or more.
[0032] The epoxy equivalent of the optional epoxy resin (A-2) is preferably in the range of 50 g / eq. to 5000 g / eq., more preferably 60 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., particularly preferably 110 g / eq. to 1000 g / eq.
[0033] The range of the weight average molecular weight (Mw) of the arbitrary epoxy resin (A-2) may be the same as the range of the weight average molecular weight (Mw) of the multifunctional liquid epoxy resin (A-1).
[0034] From the viewpoint of remarkably obtaining the effects of the present invention, it is preferred that the epoxy resin (A) such as the polyfunctional liquid epoxy resin (A-1) and the optional epoxy resin (A-2) contain no ethylenically unsaturated bond.
[0035] The (A) epoxy resin is preferably in a liquid state at 25°C. Therefore, the (A) epoxy resin may include a solid epoxy resin as any epoxy resin (A-2), but it is preferably in a liquid state at 25°C as the (A) epoxy resin as a whole. In the present specification, the (A) epoxy resin is "liquid" means that the (A) epoxy resin has fluidity. Specifically, the viscosity of the (A) epoxy resin at 25°C is preferably in the range of 100,000 mPa·s or less, more preferably 70,000 mPa·s or less, and further preferably 50,000 mPa·s or less. The lower limit of the viscosity of the (A) epoxy resin at 25°C is preferably 1 mPa·s or more, more preferably 5 mPa·s or more, and further preferably 10 mPa·s or more. The viscosity can be measured using a vibration viscometer (for example, "VM-10A-L" manufactured by Seconico Co., Ltd.). The specific method for measuring the viscosity can be the method described in the examples.
[0036] The amount of the epoxy resin (A) is preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, preferably 70% by mass or less, more preferably 65% by mass or less, and particularly preferably 60% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition. When the amount of the epoxy resin (A) is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be generally effectively reduced.
[0037] The amount of the epoxy resin (A) is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, preferably 70% by mass or less, more preferably 65% by mass or less, and particularly preferably 60% by mass or less, relative to 100% by mass of the resin component in the resin composition. When the amount of the epoxy resin (A) is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be generally effectively reduced.
[0038] [(B) Methacrylic anhydride] The resin composition involved in this embodiment includes (B) methacrylic anhydride as (B) component. (B) methacrylic anhydride can react with the epoxy group of (A) epoxy resin to form a bond, so that the resin composition can be cured. In addition, (B) methacrylic anhydride has a relatively low viscosity, so the viscosity of the resin composition can be reduced. In addition, the cured product obtained by the curing reaction including reacting (A) epoxy resin containing (A-1) multifunctional liquid epoxy resin with (B) methacrylic anhydride can have a relatively high glass transition temperature Tg.
[0039] The mass ratio represented by "(A) epoxy resin / (B) methacrylic anhydride" is preferably within a specific range. Specifically, the mass ratio of (A) epoxy resin / (B) methacrylic anhydride is preferably 20 / 80 or more, more preferably 25 / 75 or more, particularly preferably 30 / 70 or more, preferably 80 / 20 or less, more preferably 70 / 30 or less, and further preferably 60 / 40 or less. When the mass ratio of (A) epoxy resin / (B) methacrylic anhydride is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can usually be effectively reduced.
[0040] The amount of (B) methacrylic anhydride is preferably 1% by mass or more, more preferably 3% by mass or more, further preferably 5% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition. When the amount of (B) methacrylic anhydride is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can usually be effectively reduced.
[0041] The amount of methacrylic anhydride (B) is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less, relative to 100% by mass of the resin component in the resin composition. When the amount of methacrylic anhydride (B) is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can usually be effectively reduced.
[0042] [(C) Ethylenically unsaturated compound] The resin composition involved in this embodiment may contain (C) a compound containing 1 to 3 ethylenically unsaturated bonds as an arbitrary component. Hereinafter, the "(C) compound containing 1 to 3 ethylenically unsaturated bonds" as the (C) component is sometimes referred to as the "(C) ethylenically unsaturated compound". However, the (C) ethylenically unsaturated compound does not include the above-mentioned (A) component and (B) component. The ethylenically unsaturated bond, which is a non-aromatic carbon-carbon unsaturated bond, can undergo free radical polymerization, so the (C) ethylenically unsaturated compound can react to form a bond during the curing of the resin composition.
[0043] As described above, (C) ethylenically unsaturated compounds contain ethylenically unsaturated bonds in the molecule. Thus, usually (C) ethylenically unsaturated compounds contain ethylenically unsaturated groups. Ethylenically unsaturated groups represent groups containing ethylenically unsaturated bonds. Ethylenically unsaturated groups are usually monovalent groups, and examples thereof include vinyl, allyl, butenyl, maleimide, nadiimide, and (meth)acryloyl. (Meth)acryloyl includes methacryloyl, acryloyl, and combinations thereof. Among them, from the viewpoint of significantly obtaining the effect of the present invention, preferably (meth)acryloyl and vinyl, more preferably (meth)acryloyl.
[0044] The number of ethylenically unsaturated bonds contained in one molecule of the (C) ethylenically unsaturated compound is 1 or more and 3 or less, so the number of ethylenically unsaturated groups contained in one molecule of the (C) ethylenically unsaturated compound may be 1 or more and 3 or less. When the (C) ethylenically unsaturated compound contains a plurality of ethylenically unsaturated groups in one molecule, the ethylenically unsaturated groups may be the same or different.
[0045] (C) ethylenically unsaturated compounds may contain functional groups that can react with the epoxy group of (A) epoxy resin or the anhydride group of (B) methacrylic anhydride. When (C) ethylenically unsaturated compounds contain functional groups, the bonds formed by the reaction of (A) epoxy resin or (B) methacrylic anhydride with (C) ethylenically unsaturated compounds can make the cross-linked network in the cured product denser, so the glass transition temperature Tg of the cured product can be effectively increased. As functional groups, for example, epoxy groups, anhydride groups, carboxyl groups, hydroxyl groups, amino groups, isocyanate groups, etc. can be cited. Among them, it is preferably selected from one or more of epoxy groups, anhydride groups, carboxyl groups and hydroxyl groups, and epoxy groups are more preferred. The number of functional groups contained in one molecule of (C) ethylenically unsaturated compounds can be one or more. In the case of having two or more functional groups in one molecule, the functional groups can be the same or different.
[0046] Examples of the (C) ethylenically unsaturated compound not containing a functional group include (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, cyclododecyl (meth)acrylate, phenoxyethylene glycol (meth)acrylate, and neopentyl glycol di(meth)acrylate; and (meth)acrylate compounds such as styrene, α-methylstyrene, 4-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methoxystyrene, p-tert-butylstyrene, p-n-butylstyrene, and p-tert-butyl Aromatic unsaturated monomers such as oxystyrene, 2-chlorostyrene, 4-chlorostyrene, 2,4-dichlorostyrene, 1-vinylnaphthalene, divinylbenzene, 2-acetoxystyrene, 3-acetoxystyrene, 4-acetoxystyrene, 4-vinylphenylbenzoate, p-styrenesulfonic acid or its alkali metal salts (sodium salt, potassium salt, etc.); heterocyclic unsaturated monomers such as 2-vinylthiophene, N-methyl-2-vinylpyrrole, 1-vinyl-2-pyrrolidone, 2-vinylpyridine, 4-vinylpyridine, etc.; α-olefin compounds such as 1-hexene, 1-octene, 1-decene, etc.; diene compounds such as butadiene, isoprene, 4-methyl-1,4-hexadiene, 7-methyl-1,6-octadiene, etc.; etc.
[0047] As (C) ethylenically unsaturated compound containing an epoxy group, glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, allyl glycidyl ether, etc. are mentioned, for example.
[0048] Examples of the (C) ethylenically unsaturated compound containing an acid anhydride group include acrylic anhydride, maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride.
[0049] As (C) ethylenically unsaturated compound containing a carboxyl group, (meth)acrylic acid, succinic acid, cinnamic acid, crotonic acid, etc. are mentioned, for example.
[0050] Examples of the ethylenically unsaturated compound (C) containing a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, (4-hydroxymethyl)cyclohexyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2,2-dimethyl-2-hydroxyethyl (meth)acrylate, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide.
[0051] As (C) ethylenically unsaturated compound containing an amino group, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc. are mentioned, for example.
[0052] As (C) the ethylenically unsaturated compound containing an isocyanate group, 2-(meth)acryloyloxyethyl isocyanate etc. are mentioned, for example.
[0053] Among the (C) ethylenically unsaturated compounds, preferably, the (C) ethylenically unsaturated compounds containing a (meth)acryloyl group are used, more preferably, the (C) ethylenically unsaturated compounds containing a functional group and a (meth)acryloyl group are used, further preferably, the (C) ethylenically unsaturated compounds containing an epoxy group and a (meth)acryloyl group are used, further preferably, (meth)acrylate glycidyl ester and 4-hydroxybutyl (meth)acrylate glycidyl ether are used, and particularly preferably, methacrylate glycidyl ester and 4-hydroxybutyl acrylate glycidyl ether are used. The (C) ethylenically unsaturated compounds may be used alone or in combination of two or more.
[0054] The (C) ethylenically unsaturated compound is preferably in a liquid state at 25°C. In the present specification, the (C) ethylenically unsaturated compound is "liquid" means that the (C) ethylenically unsaturated compound has fluidity. Specifically, the viscosity of the (C) ethylenically unsaturated compound at 25°C is preferably 100,000 mPa·s or less. It is particularly preferred that the viscosity of the (C) ethylenically unsaturated compound at 25°C is lower, specifically, preferably 30 mPa·s or less, more preferably 20 mPa·s or less, and further preferably 10 mPa·s or less. The lower limit of the viscosity of the (C) ethylenically unsaturated compound at 25°C is not particularly limited, and may be, for example, 0.1 mPa·s or more, 0.3 mPa·s or more, 1 mPa·s or more, etc. The viscosity can be measured using a vibration viscometer (for example, "VM-10A-L" manufactured by Seconico Co., Ltd.). The specific method for measuring the viscosity can be the method described in the examples. When such a low-viscosity (C) ethylenically unsaturated compound is used, the viscosity of the resin composition can be effectively reduced. In addition, even when the viscosity of the resin composition is reduced by using the (C) ethylenically unsaturated compound, the glass transition temperature Tg of the cured product obtained from the resin composition can be increased.
[0055] (C) The weight average molecular weight (Mw) of the ethylenically unsaturated compound is preferably from 10 to 10,000, more preferably from 20 to 5,000, further preferably from 30 to 1,000, further preferably from 50 to 500.
[0056] The mass ratio represented by "{(A) epoxy resin + (B) methacrylic anhydride} / (C) ethylenically unsaturated compound" is preferably within a specific range. Specifically, the mass ratio of "{(A) epoxy resin + (B) methacrylic anhydride} / (C) ethylenically unsaturated compound" is preferably in the range of 30 / 70 or more, more preferably 40 / 60 or more, further preferably 50 / 50 or more, preferably 95 / 5 or less, more preferably 85 / 15 or less, further preferably 75 / 25 or less. When the mass ratio of "{(A) epoxy resin + (B) methacrylic anhydride} / (C) ethylenically unsaturated compound" is within the range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can usually be effectively reduced.
[0057] The amount of the ethylenically unsaturated compound (C) is preferably 1% by mass or more, more preferably 2% by mass or more, further preferably 3% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less, relative to 100% by mass of the nonvolatile components in the resin composition. When the amount of the ethylenically unsaturated compound (C) is within the range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be effectively reduced.
[0058] The amount of the ethylenically unsaturated compound (C) is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less, relative to 100% by mass of the resin component in the resin composition. When the amount of the ethylenically unsaturated compound (C) is within the range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be effectively reduced.
[0059] [(D) Epoxy polymerization accelerator] The resin composition involved in this embodiment may include (D) an epoxy polymerization accelerator as an arbitrary component. The (D) epoxy polymerization accelerator as the (D) component does not include the above-mentioned (A) to (C) components. The (D) epoxy polymerization accelerator can act as a catalyst for the reaction between the epoxy group of the (A) epoxy resin and the (B) epoxy curing agent such as methacrylic anhydride, thereby promoting the curing of the resin composition.
[0060] (D) As an epoxy polymerization accelerator, an imidazole type polymerization accelerator, an organic phosphorus type polymerization accelerator, a urea type polymerization accelerator, a guanidine type polymerization accelerator, a metal type polymerization accelerator, an amine type polymerization accelerator etc. are mentioned, for example.
[0061] Examples of the imidazole polymerization accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1') imidazole compounds such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins.
[0062] Examples of the organic phosphorus polymerization accelerator include phosphonium salts and phosphines. Examples of the phosphonium salt include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; and examples of the organic phosphorus polymerization accelerator include methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, and butyltriphenylphosphonium laurate. phosphonium salts such as benzyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate. Examples of the phosphine include aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine, tri(2,6-dimethylphenyl)phosphine, tri Aromatic phosphines such as (3,5-dimethylphenyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(2,6-dimethyl-4-ethoxyphenyl)phosphine, tri(2-methoxyphenyl)phosphine, tri(4-methoxyphenyl)phosphine, tri(4-ethoxyphenyl)phosphine, tri(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition reactants such as triphenylphosphine-p-benzoquinone addition reactants, and the like.
[0063] Examples of the urea polymerization accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, 3-(3,4-dimethylphenyl)-1, Aromatic dimethyl urea such as 1-dimethyl urea, 3-(4-isopropylphenyl)-1,1-dimethyl urea, 3-(4-methoxyphenyl)-1,1-dimethyl urea, 3-(4-nitrophenyl)-1,1-dimethyl urea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethyl urea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethyl urea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethyl urea, N,N-(1,4-phenylene)bis(N',N'-dimethyl urea), N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethyl urea) [toluenebisdimethyl urea], and the like.
[0064] Examples of the guanidine polymerization accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0065] Examples of metal polymerization accelerators include organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II) and cobalt acetylacetonate (III); organic copper complexes such as copper acetylacetonate (II); organic zinc complexes such as zinc acetylacetonate (II); organic iron complexes such as iron acetylacetonate (III); organic nickel complexes such as nickel acetylacetonate (II); organic manganese complexes such as manganese acetylacetonate (II). Examples of organic metal salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0066] Examples of the amine polymerization accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo[5.4.0]undecene.
[0067] Among the epoxy polymerization accelerators (D), organic bases are preferred, imidazole polymerization accelerators, organic phosphorus polymerization accelerators and amine polymerization accelerators are more preferred, and imidazole polymerization accelerators are still more preferred. The epoxy polymerization accelerators (D) may be used alone or in combination of two or more.
[0068] The amount of the epoxy polymerization accelerator (D) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, more preferably 0.1% by mass or more, preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 3% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition. When the amount of the epoxy polymerization accelerator (D) is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be effectively reduced.
[0069] The amount of the epoxy polymerization accelerator (D) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, more preferably 1% by mass or more, preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less, relative to 100% by mass of the resin component in the resin composition. When the amount of the epoxy polymerization accelerator (D) is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be effectively reduced.
[0070] [(E) Radical Polymerization Initiator] The resin composition involved in this embodiment may include (E) a radical polymerization initiator as an arbitrary component. The (E) radical polymerization initiator as the (E) component does not include the above-mentioned (A) to (D) components. If the (E) radical polymerization initiator is used, the radical polymerization reaction when the resin composition is cured can be promoted, so the curing time and curing temperature can be effectively adjusted.
[0071] (E) The radical polymerization initiator is preferably a thermal radical polymerization initiator capable of generating radicals by applying thermal energy. Examples of the thermal radical polymerization initiator include peroxide-based polymerization initiators and azo compound-based polymerization initiators.
[0072] Examples of the peroxide polymerization initiator include dialkyl peroxides such as di-tert-butyl peroxide, diisopropylbenzene peroxide, and tert-hexyl peroxy-2-ethylhexanoate; diacyl peroxides such as lauroyl peroxide, benzoyl peroxide, benzoyltoluoyl peroxide, and toluoyl peroxide; peroxyesters such as tert-butyl peracetate, tert-butyl peroxyoctanoate, and tert-butyl peroxybenzoate; ketone peroxide compounds; peroxycarbonate compounds; peroxyketal compounds such as 1,1-di(tert-amylperoxy)cyclohexane; and the like.
[0073] Examples of the azo compound polymerization initiator include azonitrile compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile); azoamide compounds such as 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}; and , azo amidine compounds such as 2'-azobis(2-amidinopropane) dihydrochloride and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride; azoalkane compounds such as 2,2'-azobis(2,4,4-trimethylpentane) and 4,4'-azobis(4-cyanovaleric acid); azo compounds having an oxime skeleton such as 2,2'-azobis(2-methylpropionamide oxime); 2,2'-azobis(isobutyric acid) dimethyl ester; etc.
[0074] Among the above-mentioned (E) radical polymerization initiators, peroxide-based polymerization initiators are preferred. The radical polymerization initiators may be used alone or in combination of two or more.
[0075] The amount of the (E) radical polymerization initiator is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.05% by mass or more, preferably 5% by mass or less, more preferably 2% by mass or less, and particularly preferably 1% by mass or less, relative to 100% by mass of the non-volatile components in the resin composition. When the amount of the (E) radical polymerization initiator is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be effectively reduced.
[0076] The amount of the (E) radical polymerization initiator is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.2% by mass or more, preferably 10% by mass or less, more preferably 6% by mass or less, and particularly preferably 3% by mass or less, relative to 100% by mass of the resin component in the resin composition. When the amount of the (E) radical polymerization initiator is within the above range, the viscosity of the resin composition can be reduced and the glass transition temperature of the cured product can be increased at a high level, and the thermal expansion of the cured product can be effectively reduced.
[0077] [(F) Inorganic filler] The resin composition involved in the present embodiment may contain (F) inorganic filler as an arbitrary component. The (F) inorganic filler as the (F) component does not include the above-mentioned (A) to (E) components. The (F) inorganic filler is usually contained in the resin composition in the form of particles. If the (F) inorganic filler is used, the linear thermal expansion coefficient of the cured product of the resin composition can be suppressed, so effective suppression of thermal expansion can be achieved. In addition, the resin composition involved in the present embodiment can also obtain a lower viscosity when containing the (F) inorganic filler. In particular, the resin component of the resin composition involved in the present embodiment can have a lower viscosity, so when a large amount of (F) inorganic filler is included, the resin composition can also have a lower viscosity. Therefore, even when a large amount of (F) inorganic filler is included, low viscosity and high glass transition temperature can be achieved at a high level.
[0078] As the material of (F) inorganic filler, inorganic compounds can be used. As examples of (F) inorganic filler, for example, silica, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc. can be cited. Among them, preferably silica. As silica, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. can be cited. In addition, as silica, preferably spherical silica.
[0079] Examples of commercially available inorganic fillers (F) include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical Materials Co., Ltd., "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", "SO-C1", and "SC-C2" manufactured by Yaduma Co., Ltd., "UFP-20", "UFP-30", "DAW-03", and "FB-105FD" manufactured by DENKA Corporation, "SILFIL NSS-3N", "SILFIL NSS-4N", and "SILFIL NSS-5N" manufactured by Tokuyama Co., Ltd., and "AEROSIL 200", "AEROSIL R805", and "AEROSIL RY300" manufactured by Nippon Aerosil Co., Ltd. The inorganic filler (F) may be used alone or in combination of two or more.
[0080] Regarding the range of the average particle size of the (F) inorganic filler, from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferably 0.01 μm or more, more preferably 0.1 μm or more, further preferably 1 μm or more, preferably 20 μm or less, more preferably 15 μm or less, further preferably 10 μm or less.
[0081] (F) The average particle size of the inorganic filler can be measured by the laser diffraction scattering method based on Mie scattering theory. Specifically, the particle size distribution of the inorganic filler can be made into a volume basis by a laser diffraction scattering particle size distribution measuring device, and the median particle size can be measured as the average particle size. The sample can be measured using a sample obtained by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. For the sample, a laser diffraction particle size distribution measuring device can be used, using a light source wavelength using blue and red, and the particle size distribution of the volume basis of the inorganic filler can be measured in a flow cell manner, and the average particle size can be calculated as the median particle size according to the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba Manufacturing Co., Ltd. can be cited.
[0082] The maximum particle size of the inorganic filler (F) is preferably 0.01 μm or more, more preferably 0.1 μm or more, further preferably 1 μm or more, preferably 100 μm or less, more preferably 50 μm or less, and further preferably 30 μm or less, from the viewpoint of significantly obtaining the desired effect of the present invention. The maximum particle size of the inorganic filler (F) can be measured based on the particle size distribution obtained by the laser diffraction scattering method.
[0083] The specific surface area of the inorganic filler (F) is preferably within a range of 0.1 m / s from the viewpoint of significantly obtaining the desired effect of the present invention. 2 / g or more, preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 / g or more, preferably 100m 2 / g or less, preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 The specific surface area of the inorganic filler can be measured by adsorbing nitrogen gas on the surface of a sample using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method and calculating the specific surface area by the BET multipoint method.
[0084] From the viewpoint of improving moisture resistance and dispersibility, (F) inorganic filler is preferably treated by a surface treatment agent. As the surface treatment agent, for example, aminosilane coupling agents, urea silane coupling agents, epoxy silane coupling agents, mercapto silane coupling agents, vinyl silane coupling agents, styryl silane coupling agents, acrylate silane coupling agents, isocyanate silane coupling agents, thioether silane coupling agents, organosilazane compounds, titanate coupling agents, alkoxy silanes, etc. can be cited.
[0085] Examples of commercially available surface treatment agents include "KBM22" (dimethyldimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM403" (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd. "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM5783" (N-phenyl-3-aminooctyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM103" (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-4803" (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd., etc. The surface treatment agent may be used alone or in any combination of two or more.
[0086] From the viewpoint that the dispersibility of the inorganic filler material is improved, the degree of the surface treatment performed by the surface treatment agent is preferably within a specific range. Specifically, 100% by mass of the inorganic filler material is preferably surface treated with a surface treatment agent of 0.2% by mass to 5% by mass, more preferably surface treated with a surface treatment agent of 0.2% by mass to 3% by mass, and further preferably surface treated with a surface treatment agent of 0.3% by mass to 2% by mass.
[0087] The degree of surface treatment by the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. The amount of carbon per unit surface area of the inorganic filler is preferably 0.02 mg / m2 from the viewpoint of improving the dispersibility of the inorganic filler. 2 More than 0.1 mg / m 2 More preferably, 0.2 mg / m 2 More than 1.0 mg / m 2 Below, preferably 0.8mg / m 2 Below, more preferably 0.5 mg / m 2 the following.
[0088] (F) The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added as a solvent to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid component, a carbon analyzer can be used to measure the amount of carbon per unit surface area of the inorganic filler. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. can be used.
[0089] About the scope of the amount of (F) inorganic filler, relative to 100 mass % of the non-volatile component of the resin combination, preferably more than 40 mass %, more preferably more than 50 mass %, particularly preferably more than 60 mass %, preferably less than 95 mass %, more preferably less than 92 mass %, further more preferably less than 90 mass %. (F) When the amount of inorganic filler is within the scope, the reduction of the viscosity of the resin combination and the increase of the glass transition temperature of the cured product can be achieved at a high level, and then the thermal expansion of the cured product can be effectively reduced usually.
[0090] [(G) Organic filler] The resin composition involved in this embodiment may contain (G) an organic filler as an arbitrary component. The (G) organic filler as the (G) component does not include the above-mentioned (A) to (F) components. If the (G) organic filler is used, the mechanical strength such as the toughness of the cured product can be improved.
[0091] (G) organic filler exists in the resin composition in the form of particles, and is usually contained in the cured product under the state of maintaining its particle-like form. As (G) organic filler, an organic filler that can be used when forming an insulating material of electronic components such as semiconductor chip packaging and printed wiring boards can be used. As (G) organic filler, for example, rubber particles, polyamide microparticles, organosilicon particles, liquid crystal polymer powder (LCP powder), polyphenylene sulfide powder (PPS powder) etc. can be cited. Among them, preferably organosilicon particles.
[0092] Examples of the organosilicon material contained in the organosilicon particles include polysiloxane compounds. Examples of the polysiloxane compound include polydialkylsiloxanes such as polydimethylsiloxane, polydiarylsiloxanes such as polydiphenylsiloxane, polyalkylarylsiloxanes such as polymethylphenylsiloxane, polydialkyl-diarylsiloxanes such as polydimethyl-diphenylsiloxane, polydialkyl-alkylarylsiloxanes such as polydimethyl-methylphenylsiloxane, and polydiaryl-alkylarylsiloxanes such as polydiphenyl-methylphenylsiloxane. The polysiloxane compound may have a crosslinked structure. Commercially available silicone particles include, for example, "KMP-600", "KMP-601", "KMP-602", "KMP-605", and "X-52-7030" (silicone rubber particles coated with silicone resin) manufactured by Shin-Etsu Chemical Co., Ltd.; "KMP-597", "KMP-598", "KMP-594", and "X-52-875" (non-coated silicone rubber particles) manufactured by Shin-Etsu Chemical Co., Ltd.
[0093] (G) The organic filler may be used alone or in combination of two or more.
[0094] About (G) the average particle size of organic filler, from the viewpoint of significantly obtaining the desired effect of the present invention, preferably more than 0.005 μm, more preferably more than 0.2 μm, preferably less than 100 μm, more preferably less than 15 μm. (G) The average particle size of organic filler can be measured using dynamic light scattering. For example, the organic filler can be uniformly dispersed in a suitable organic solvent by ultrasound, using a concentrated particle size analyzer ("FPAR-1000" made by Otsuka Electronics Co., Ltd.), the particle size distribution of the organic filler is made on a mass basis, and the median particle size is measured as the average particle size.
[0095] Regarding the range of the amount of the (G) organic filler, relative to 100 mass % of the non-volatile component in the resin composition, it is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, further preferably 1 mass % or more, preferably 30 mass % or less, more preferably 20 mass % or less, and particularly preferably 10 mass % or less.
[0096] Regarding the range of the amount of the (G) organic filler, relative to 100 mass % of the resin component in the resin composition, it is preferably 1 mass % or more, more preferably 5 mass % or more, further preferably 10 mass % or more, preferably 40 mass % or less, more preferably 30 mass % or less, and particularly preferably 20 mass % or less.
[0097] [(H) Optional additives] As long as the effect of the present invention is not significantly impaired, the resin composition involved in this embodiment may further contain (H) any additive as an arbitrary component. As (H) any additive, for example: thermoplastic resin; epoxy curing agents such as phenolic curing agents, benzoxazine curing agents, acid anhydride curing agents, cyanate curing agents, and active ester curing agents; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as Benton (bentonite) and montmorillonite; defoaming agents such as silicone defoaming agents, acrylic defoaming agents, fluorine defoaming agents, and vinyl resin defoaming agents; ultraviolet absorbers such as benzotriazole ultraviolet absorbers; adhesion enhancers such as urea silane; triazole adhesion imparting agents Adhesion imparting agents such as agents, tetrazole adhesion imparting agents, triazine adhesion imparting agents; antioxidants such as hindered phenol antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine surfactants and silicone surfactants; flame retardants such as phosphorus flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen flame retardants (such as melamine sulfate), halogen flame retardants, inorganic flame retardants (such as antimony trioxide); dispersants such as phosphate dispersants, polyoxyalkylene dispersants, acetylene dispersants, silicone dispersants, anionic dispersants, cationic dispersants; stabilizers such as borate stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, carboxylic anhydride stabilizers, etc.
[0098] [(I) Organic solvent] The resin composition involved in the present embodiment may contain (I) an organic solvent as an arbitrary component, or may not contain (I) an organic solvent. (I) An organic solvent refers to a compound having a boiling point of 250°C or less at 1 atmosphere, which is non-radical polymerizable and non-reactive with the non-volatile components in the resin composition. In the past, organic solvents were often used to reduce the viscosity of the resin composition. In contrast, the resin composition involved in the present embodiment can be a low-viscosity liquid resin composition even when it does not contain (I) an organic solvent or when the (I) organic solvent is a small amount.
[0099] From the viewpoint of suppressing the viscosity change of the resin composition caused by the volatilization of the organic solvent (I) and the viewpoint of the operating environment, the organic solvent (I) is preferably a small amount. The specific range of the amount of the organic solvent (I) is preferably less than 3% by mass, more preferably less than 2% by mass, further more preferably less than 1% by mass, and particularly preferably 0% by mass, relative to 100% by mass of the resin composition.
[0100] [Characteristics of resin composition] The resin composition involved in this embodiment is in liquid state at 25°C. In this specification, the resin composition being "liquid" means that the resin composition has fluidity. Specifically, the viscosity of the resin composition at 25°C is usually in the range of 100,000 mPa·s or less, preferably 1000 mPa·s or less. If the resin composition involved in this embodiment is adopted, the viscosity can be reduced, so the viscosity of the resin composition at 25°C is preferably smaller. In general, the viscosity of the resin composition may vary greatly depending on the presence or absence of (F) inorganic filler. Therefore, the range of the viscosity of the resin composition is described below according to the presence or absence of (F) inorganic filler.
[0101] First, the case where the resin composition does not contain (F) an inorganic filler is described. The viscosity of the resin composition not containing (F) an inorganic filler at 25° C. is preferably 30 mPa·s or less, more preferably 25 mPa·s or less, and further preferably 20 mPa·s or less. The lower limit is not particularly limited, and may be, for example, 1 mPa·s or more, 3 mPa·s or more, 5 mPa·s or more, etc.
[0102] The viscosity range of the resin component of the resin composition not containing the (F) inorganic filler (i.e., the component after removing the (I) organic solvent from the resin composition) at 25°C may be the same as the viscosity range of the resin composition not containing the (F) inorganic filler described above at 25°C.
[0103] Second, the case where the resin composition contains (F) an inorganic filler is described. The viscosity of the resin composition containing (F) an inorganic filler at 25°C is preferably 1000 mPa·s or less, more preferably 700 mPa·s or less, further preferably 500 mPa·s or less, and particularly preferably less than 200 mPa·s. The lower limit is not particularly limited, and may be, for example, 1 mPa·s or more, 3 mPa·s or more, 5 mPa·s or more, etc.
[0104] In addition, the range of viscosity at 25°C of the resin component of the resin composition containing the (F) inorganic filler (i.e., the component after removing the (F) inorganic filler and the (I) organic solvent from the resin composition) may be the same as the range of viscosity at 25°C of the above-mentioned resin composition not containing the (F) inorganic filler.
[0105] Furthermore, the viscosity range of the component after removing the (F) inorganic filler from the resin composition containing the (F) inorganic filler at 25°C may be the same as the viscosity range of the resin composition not containing the (F) inorganic filler at 25°C described above.
[0106] The viscosity of the resin composition, the resin component, and the component after removing the (F) inorganic filler from the resin composition can be measured using a vibration viscometer (for example, "VM-10A-L" manufactured by CENIC CO., LTD.) The specific method for measuring the viscosity can be the method described in the Examples.
[0107] Conventional resin compositions generally achieve low viscosity by including a large amount of organic solvents. However, conventional resin compositions including a large amount of organic solvents like this have a tendency that viscosity increases over time due to the volatilization of the organic solvent. In contrast, the resin composition involved in the present embodiment can reduce the amount of (I) organic solvent, preferably can be free of (I) organic solvent. Therefore, the viscosity increase caused by the volatilization of (I) organic solvent can usually be suppressed. Viscosity increase can be suppressed, and the viscosity increase rate can be used to represent.
[0108] For example, the viscosity η0 of the resin composition is measured at 25°C. Then, the resin composition is placed at 25°C for 1 hour. The viscosity η1 of the resin composition after placement is measured at a temperature of 25°C. The viscosity η1 after placement is divided by the viscosity η0 before placement to determine the viscosity increase rate η1 / η0. The viscosity increase rate η1 / η0 is preferably less than 200%, more preferably less than 160%, further preferably less than 130%, and preferably more than 100%. The specific method for measuring the viscosity increase rate can be the method described in the examples.
[0109] By curing the resin composition involved in the present embodiment, a cured product can be obtained. During the curing, heat is usually applied to the resin composition. Therefore, among the components contained in the resin composition, the (I) organic solvent as a volatile component can volatilize due to the heat during curing. Therefore, the cured product of the resin composition can include the non-volatile components of the resin composition or its reaction product.
[0110] The cured product of the resin composition according to the present embodiment may have a relatively high glass transition temperature Tg. The specific glass transition temperature Tg of the cured product is preferably 150°C or higher, more preferably 160°C or higher, and further preferably 170°C or higher. The higher the upper limit, the better, and may be, for example, 220°C or lower, 210°C or lower, 200°C or lower, etc.
[0111] The glass transition temperature of the cured product of the resin composition can be measured using a viscoelasticity measuring device ("DMA7100" manufactured by Hitachi, Ltd.). During the measurement, the stretching conditions may be a strain amplitude of 10 μm, a minimum tension of 0 mN, a tension gain of 1.5, an initial value of a force amplitude of 10 mN, and 1 Hz. In addition, when the resin composition is cured in order to measure the glass transition temperature of the cured product, the curing conditions may be a curing temperature of 100 ° C and a curing time of 5 hours. The specific method for measuring the glass transition temperature Tg may be the method described in the embodiment.
[0112] Generally, the cured product of the resin composition involved in the present embodiment can realize a cured product with small thermal expansion. Specifically as follows. Here, in the use temperature range of the general cured product from room temperature to about 260°C, the temperature range below the glass transition temperature Tg of the cured product is referred to as the "low temperature range", and the temperature range above the glass transition temperature Tg is referred to as the "high temperature range". The linear thermal expansion coefficient of the cured product of the resin composition is generally relatively small in the low temperature range below the glass transition temperature, and relatively large in the high temperature range above the glass transition temperature. Therefore, the cured product with a high glass transition temperature Tg can narrow the high temperature range with a relatively large linear thermal expansion coefficient, so the thermal expansion of the entire use temperature range can be reduced. The cured product of the resin composition involved in the present embodiment can have a higher glass transition temperature Tg as described above, so the thermal expansion can usually be reduced. And, because the thermal expansion can be reduced like this, the cracks and peeling of the cured product can be suppressed.
[0113] In addition, the cured product of the resin composition involved in the present embodiment can have a smaller average linear thermal expansion coefficient in the low temperature range and the high temperature range. Furthermore, the resin component of the resin composition can usually have a lower viscosity, so even in the case of containing (F) inorganic filler, the resin composition can also have a lower viscosity. Thus, the resin composition containing (F) inorganic filler can make the average linear thermal expansion coefficient of its cured product smaller by (F) inorganic filler while having a lower viscosity.
[0114] For example, the average linear thermal expansion coefficient CTEα1 of the cured product measured in the first measurement range of 40°C to 60°C is preferably less than 50 ppm / °C, more preferably 40 ppm / °C or less, and further preferably 30 ppm / °C or less. The lower limit is not particularly limited, and may be, for example, 1 ppm / °C or more, 5 ppm / °C or more, etc.
[0115] In addition, for example, when the cured product has a glass transition temperature Tg of 220°C or less, the average linear thermal expansion coefficient CTEα2 of the cured product in the second measurement range of Tg+40°C to 260°C is preferably less than 100 ppm / °C, more preferably 80 ppm / °C or less, and further preferably 60 ppm / °C or less. The lower limit is not particularly limited, and may be, for example, 1 ppm / °C or more, 10 ppm / °C or more, etc.
[0116] The average linear thermal expansion coefficient of the cured product of the resin composition can be measured by thermomechanical analysis using a tensile load method. The measurement can be performed twice continuously under the measurement conditions of a load of 1 g and a heating rate of 5°C / min, and the average linear thermal expansion coefficient is measured based on the second measurement. In addition, when the resin composition is cured in order to measure the average linear thermal expansion coefficient of the cured product, the curing conditions may be a curing temperature of 100°C and a curing time of 5 hours. The specific method for measuring the average linear thermal expansion coefficient can be the method described in the examples.
[0117] [Method for producing resin composition] The resin composition can be manufactured by a method including mixing the essential components of the above-mentioned components. During mixing, mixing or stirring can be carried out by a mixing device such as a three-roll mill, a ball mill, a bead mill, a sand mill, or a stirring device such as a super mixer or a planetary mixer. In addition, all or part of the above-mentioned components can be mixed simultaneously or sequentially. Furthermore, during the mixing of the components, cooling or heating can be carried out.
[0118] [Application of resin composition] The resin composition involved in the present embodiment can be used for various purposes such as laminated material, casting material, film material, adhesive, prepreg material. For example, when the resin composition is used as a prepreg material, the prepreg can be obtained by impregnating the resin composition in a fiber substrate and curing the impregnated resin composition. As a fiber substrate, for example, carbon fiber, glass fiber, aramid fiber, boron fiber, aluminum oxide fiber, silicon carbide fiber, etc. can be used.
[0119] In addition, the resin composition involved in the present embodiment can be used as a forming material for a circuit substrate. As examples of specific uses, there can be cited: a forming material for an insulating layer of a circuit substrate; solder resist, a buffer coating, a bottom filling material, a chip bonding material, a semiconductor sealing material, a hole-filling resin, a component embedding resin, etc. As a circuit substrate, for example: semiconductor chip packages such as multi-chip packages, stacked packages, wafer-level packages, panel-level packages, and system-level packages can be cited; printed wiring boards such as rigid substrates, flexible substrates, single-sided laminated substrates, thin substrates, and component-built-in substrates; etc. If these uses are adopted, a circuit substrate containing a cured product of a resin composition can be obtained.
[0120] Wherein, from the viewpoint of the excellent viscosity and the excellent glass transition temperature of the cured product of the resin composition effectively utilizing the present embodiment, the resin composition is preferably used as bottom filling material. The bottom filling material is usually used to fill the gap between the substrate and the semiconductor chip. Particularly from the viewpoint of effectively utilizing low viscosity, the resin composition involved in the present embodiment can be well used as the bottom filling material for the back coating method (capillary bottom filling (capillaryunderfill) method).
[0121] To give specific examples, the resin composition involved in this embodiment can be used as: a bottom filling material for filling the gap between the redistribution layer and the semiconductor chip, a bottom filling material for filling the gap between the substrate and the redistribution layer, a bottom filling material for a semiconductor device including a multi-die package (bottom filling material for a semiconductor device including a multi-chip package), a bottom filling material for a semiconductor device including a fan-out package (bottom filling material for a semiconductor device including a fan-out package), a bottom filling material for a semiconductor device including a semiconductor package containing a silicon interposer (bottom filling material for a semiconductor device including a semiconductor package containing a silicon interposer), a bottom filling material for a semiconductor device including two or more semiconductor chips overlapping in the thickness direction through silicon vias (bottom filling material for a semiconductor device including a semiconductor chip package including two or more semiconductor chips overlapping in the thickness direction through silicon vias), etc.
[0122] [Semiconductor chip packaging] The resin composition according to the present embodiment can be used to manufacture a semiconductor chip package. The semiconductor chip package includes a cured product of the resin composition. Generally, the semiconductor chip package includes: a substrate, a semiconductor chip disposed on the substrate with a gap, and a cured product of the resin composition filling the gap. The following is an example of the semiconductor chip package illustrated in the accompanying drawings.
[0123] Figure 1 FIG. 1 is a cross-sectional view schematically showing a semiconductor chip package 1 according to a first example of the present invention. Figure 1 As shown, the semiconductor chip package 1 according to the first example includes a substrate 10 , a semiconductor chip 30 provided on the substrate 10 with a gap therebetween, and a cured product 20 of a resin composition filling the gap between the substrate 10 and the semiconductor chip 30 .
[0124] The semiconductor chip package can be produced, for example, by using the above-mentioned resin composition as an underfill material and by a method comprising the following steps (1) to (3). Steps (1) to (3) are preferably performed in the order of step (1), step (2), and step (3). (1) A step of placing a semiconductor chip on a substrate, (2) a step of filling a gap between a substrate and a semiconductor chip with a resin composition, and (3) A step of curing the resin composition.
[0125] In step (1), a semiconductor chip is provided on a substrate. The substrate may be any of various substrates that can be used to form a semiconductor chip package. Typically, the substrate has a circuit wiring that connects the terminal electrodes of the semiconductor chip. The substrate may have one or both of a conductor layer and an insulating layer on one or both sides thereof. Furthermore, the conductor layer and the insulating layer may be patterned.
[0126] As a method of arranging a semiconductor chip on a substrate, for example, a method of forming bumps on the substrate or the semiconductor chip can be adopted. The method of forming the bumps can be implemented according to a method known to those skilled in the art used in the manufacture of semiconductor chip packages.
[0127] The semiconductor chip is usually placed on the substrate under conditions that allow the terminal electrodes of the semiconductor chip to be conductively connected to the circuit wiring of the substrate. For example, the semiconductor chip can be placed under conditions used in flip-chip mounting.
[0128] As a setting method, for example, a method of crimping a semiconductor chip to a substrate can be cited. In the crimping conditions, the crimping temperature is usually in the range of 120°C to 240°C, preferably in the range of 130°C to 200°C, and more preferably in the range of 140°C to 180°C. In addition, the crimping time is usually in the range of 1 second to 60 seconds, preferably 5 seconds to 30 seconds. Furthermore, as a setting method, for example, a method of placing a semiconductor chip on a substrate and performing reflow soldering can also be cited. The reflow soldering conditions can be set to the range of 120°C to 300°C.
[0129] When a semiconductor chip is provided on a substrate, a gap is formed between the substrate and the semiconductor chip. The thickness of the gap is preferably 600 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less. The lower limit is not particularly limited and may be 1 μm or more.
[0130] In step (2), the gap between the substrate and the semiconductor chip is filled with a resin composition. As mentioned above, the resin composition involved in this embodiment can be low-viscosity, so the resin composition can be quickly filled. As a filling method of the resin composition, for example, a method of supplying the resin composition near the side end of the semiconductor chip and filling the gap with the resin composition using a capillary phenomenon can be cited.
[0131] In step (3), the resin composition is cured to obtain a cured product of the resin composition in the gap. The curing conditions of the resin composition are not particularly limited, and for example, the conditions used when forming an insulating layer of a printed wiring board can be used.
[0132] The specific curing conditions of the resin composition may vary depending on the type of the resin composition, etc. In one example, the curing temperature is preferably 50° C. to 250° C., more preferably 60° C. to 240° C., and further preferably 100° C. to 200° C. The curing time is preferably 5 minutes to 600 minutes, more preferably 10 minutes to 500 minutes, and further preferably 15 minutes to 400 minutes.
[0133] Before curing the resin composition, the resin composition may be preheated at a temperature lower than the curing temperature. For example, before curing the resin composition, the resin composition may be preheated at a temperature of usually 40°C to 120°C, preferably 50°C to 115°C, and more preferably 60°C to 110°C. The preheating time is usually 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes.
[0134] Figure 2 FIG. 1 is a cross-sectional view schematically showing a semiconductor chip package 100 according to a second example of the present invention. Figure 2 As shown, the semiconductor chip package 100 involved in the second example includes: a substrate 11, a plurality of semiconductor chips 31 arranged on the substrate 11 via bumps 41, and a cured product 21 of a resin composition that fills the gap between the substrate 11 and the plurality of semiconductor chips 31. The resin composition involved in this embodiment can be made low in viscosity, so the resin composition can quickly fill the gap even in a multi-chip package having a plurality of semiconductor chips. The semiconductor chip package 100 involved in the second example can be manufactured by a method including steps (1) to (3) in the same manner as the semiconductor package involved in the first example.
[0135] Figure 3 2 is a cross-sectional view schematically showing a semiconductor chip package 200 according to a third embodiment of the present invention. The semiconductor chip package 200 according to the third embodiment is a fan-out type package. Figure 3 As shown, it includes: a substrate 12, a semiconductor chip 32 arranged on the substrate 12 via bumps 42, a cured product 22 of a resin composition filling a gap between the substrate 12 and the semiconductor chip 32, and a sealing layer 51 formed in a manner covering the periphery of the semiconductor chip 32. The resin composition involved in this embodiment can be made low in viscosity, so that even in a large fan-out package 200, the resin composition can quickly fill the gap. The semiconductor chip package 200 involved in the third example can be manufactured by a method including the above-mentioned steps (1) to (3) and a step of forming a sealing layer.
[0136] As the sealing material for sealing layer, the resin combination involved in the present embodiment can be used, and other sealing materials can also be used.In general, the sealing material for sealing layer comprises a large amount of inorganic filling materials.In addition, the resin combination involved in the present embodiment can comprise a large amount of inorganic filling materials while maintaining low viscosity.Therefore, the sealing layer and the cured product of the resin combination as the bottom filling material can all comprise a large amount of inorganic filling materials.In this case, the degree of thermal expansion of the sealing layer and the bottom filling material can be made to be equal, so cracks can be suppressed on the interface of the two.
[0137] Figure 4 FIG. 4 is a cross-sectional view schematically showing a semiconductor chip package 300 according to a fourth example of the present invention. Figure 4 As shown, the semiconductor chip package 300 involved in the fourth example includes: a substrate 13, a rewiring layer 61 provided on the substrate 13 via bumps 43, a semiconductor chip 33 provided on the rewiring layer 61 via bumps 44, and cured products 23a and 23b of the resin composition. In the semiconductor chip package 300, a gap between the substrate 13 and the rewiring layer 61, and a gap between the rewiring layer 61 and the semiconductor chip 33 are formed between the substrate 13 and the semiconductor chip 33. The gap between the substrate 13 and the rewiring layer 61 is filled with the cured product 23a of the resin composition, and the gap between the rewiring layer 61 and the semiconductor chip 33 is filled with the cured product 23b of the resin composition, so that the gaps formed between the substrate 13 and the semiconductor chip 33 are both filled with the cured products 23a and 23b. As shown Figure 4 As shown, the semiconductor chip package 300 may have a plurality of semiconductor chips 33. Figure 4 As shown, the semiconductor chip package 300 may include bumps 49 on the surface of the substrate 13 opposite to the surface on the semiconductor chip 33 side. The cured product 23a and the cured product 23b may be cured products of the same resin composition or cured products of different resin compositions.
[0138] For the rewiring layer, for example, a first resin layer, a conductor layer, and a second resin layer may be provided in order from the substrate side. The first resin layer and the second resin layer may contain polyimide resin, or may only contain polyimide resin. The material of the conductor layer may contain, for example, one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor layer may be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (for example, a nickel-chromium alloy, a copper-nickel alloy, and a copper-titanium alloy) may be cited. Among them, from the viewpoint of versatility, cost, and ease of pattern formation of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, and a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is more preferred. Through holes (not shown) may be provided in the first resin layer and the second resin layer as needed, and the semiconductor chip and the circuit wiring of the substrate may be electrically connected via the through holes. The semiconductor chip package involved in the fourth example can be manufactured by a method including the above-mentioned steps (1) to (3) and the step of forming a rewiring layer. If the semiconductor chip package involved in the fourth example is adopted, the same advantages as the semiconductor chip packages involved in the first to third examples can be obtained.
[0139] Figure 5 FIG. 4 is a cross-sectional view schematically showing a semiconductor chip package 400 according to a fifth example of the present invention. Figure 5 As shown, the semiconductor chip package 400 involved in the fifth example includes: a substrate 14, a silicon interposer 80 provided on the substrate 14 via bumps 45, a semiconductor chip 34 provided on the silicon interposer 80 via bumps 46, and cured products 24a and 24b of a resin composition. In the semiconductor chip package 400, a gap between the substrate 14 and the silicon interposer 80, and a gap between the silicon interposer 80 and the semiconductor chip 34 are formed between the substrate 14 and the semiconductor chip 34. The gap between the circuit substrate 14 and the silicon interposer 80 is filled with the cured product 24a of the resin composition, and the gap between the silicon interposer 80 and the semiconductor chip 34 is filled with the cured product 24b of the resin composition, so that the gaps formed between the substrate 14 and the semiconductor chip 34 are filled with the cured products 24a and 24b. From the viewpoint of electrically connecting the substrate 14 and the semiconductor chip 34, a through hole 71 may be formed in the silicon interposer 80. As shown in FIG. Figure 5 As shown, the semiconductor chip package 400 may include a plurality of semiconductor chips 34. In addition, the cured product 24a and the cured product 24b may be cured products of the same resin composition or cured products of different resin compositions.
[0140] The semiconductor chip package of the fifth example can be manufactured by a method including the above steps (1) to (3) and the step of forming a silicon interposer. If the semiconductor chip package of the fifth example is used, the same advantages as those of the semiconductor chip packages of the first to fourth examples can be obtained.
[0141] Figure 6 FIG. 5 is a schematic cross-sectional view of a semiconductor chip package 500 according to a sixth embodiment of the present invention. Figure 6 As shown, the semiconductor chip package 500 involved in the sixth example includes: a substrate 15, a silicon interposer 81 provided on the substrate 15 via bumps 47, a semiconductor chip 35 and a chip stack 36 provided on the silicon interposer 81 via bumps 48, and cured products 25a and 25b of a resin composition. In the semiconductor chip package 500, a gap between the substrate 15 and the silicon interposer 81, and a gap between the silicon interposer 81 and the semiconductor chip 35 and the chip stack 36 are formed between the substrate 15 and the semiconductor chip 35 and the chip stack 36. The gap between the substrate 15 and the silicon interposer 81 is filled with the cured product 25a of the resin composition, and the gap between the silicon interposer 81 and the semiconductor chip 35 and the chip stack 36 is filled with the cured product 25b of the resin composition, so that the gaps formed between the substrate 15 and the semiconductor chip 35 and the chip stack 36 are filled with the cured products 25a and 25b. The chip stack 36 includes two or more semiconductor chips overlapping in the thickness direction, and these overlapping semiconductor chips are electrically connected through silicon vias 37. In addition, from the viewpoint of electrically connecting the substrate 15, the semiconductor chip 35 and the chip stack 36, the silicon interposer 81 may be formed with a through hole 72. Furthermore, the cured product 25a and the cured product 25b may be cured products of the same resin composition or cured products of different resin compositions.
[0142] The semiconductor chip package of the sixth example can be manufactured by a method including the above-mentioned steps (1) to (3), the step of forming a silicon interposer, and the step of setting a chip stack. If the semiconductor chip package of the sixth example is adopted, the same advantages as the semiconductor chip packages of the first to fifth examples can be obtained.
[0143] [Semiconductor devices] The semiconductor chip package described above can be used for manufacturing semiconductor devices. The semiconductor device includes a semiconductor chip package. Examples of semiconductor devices include various semiconductor devices for electrical products (such as computers, mobile phones, digital cameras, and televisions) and transportation vehicles (such as motorcycles, cars, trams, ships, and aircraft). Example
[0144] The present invention is specifically described below with reference to the examples, but the present invention is not limited to these examples. It should be noted that in the following description, unless otherwise expressly stated, the "parts" and "%" indicating the amount refer to "parts by mass" and "% by mass", respectively. In addition, unless otherwise expressly stated, the operations described below are performed in an atmosphere at normal temperature and pressure (25° C., 1 atm).
[0145] <Example 1: Production of resin composition 1> 52.0 parts of a mixed resin of bisphenol A epoxy resin and bisphenol F epoxy resin ("ZX-1059" manufactured by Nippon Steel Chemical Materials Co., Ltd., epoxy equivalent of about 160 g / eq. to 170 g / eq.) and 48.0 parts of methacrylic anhydride were mixed and stirred. 2.0 parts of an organic base (2-ethyl-4-methylimidazole, "2E4MZ" manufactured by Shikoku Chemicals Co., Ltd.) as an epoxy polymerization accelerator and 0.5 parts of a radical polymerization initiator ("PERHEXYL O" manufactured by NOF Corporation) were added thereto and uniformly dispersed using a high-speed rotary mixer to prepare a resin composition 1. The resin composition 1 was in a liquid state at 25°C.
[0146] <Examples 2 to 15 and Comparative Examples 1 to 3: Production of Resin Compositions 2 to 18> Resin compositions 2 to 18 were prepared in the same manner as in Example 1 except that the types and proportions of the materials of the resin compositions were changed as shown in Tables 1 and 2 below. Resin compositions 2 to 15 and 17 to 18 were liquid at 25° C. Resin composition 16 was liquid at 25° C., but had a relatively high viscosity.
[0147] <Measurement of viscosity (initial viscosity) of resin composition> In Examples 1 to 15 and Comparative Examples 2 to 3, the viscosity of the resin compositions 1 to 15 and 17 to 18 was measured using a vibration viscometer ("VM-10A-L" manufactured by Seconic Corporation) while maintaining the temperature at 25°C ± 2°C immediately after production. The viscosity of the resin composition immediately after production measured in this manner may be referred to as "initial viscosity" hereinafter.
[0148] Since the resin composition 16 prepared in Comparative Example 1 had a high viscosity, the initial viscosity could not be measured by the vibration viscometer. Therefore, the initial viscosity of only the resin composition 16 was measured at 25° C. and 2 rpm using a viscosity / viscoelasticity measuring device (“HAAKE Rheo Stress 6000” manufactured by Thermo Scientific).
[0149] <Measurement of viscosity increase rate of resin composition> 1 g of each resin composition was weighed into an aluminum cup using a precision balance ("XS225DUV" manufactured by METTLER TOLEDO), and the mixture was left on a hot plate controlled at 25° C. for 1 hour.
[0150] Among the resin compositions after standing, the viscosity η1 of the resin compositions 1 to 15 and 18 prepared in Examples 1 to 15 and Comparative Example 3 was measured using a vibration viscometer (“VM-10A-L” manufactured by Seconic Corporation) while maintaining the temperature at 25±2° C. The viscosity η1 of the resin composition after standing measured in this way may be referred to as “viscosity after standing”.
[0151] Since the resin compositions 16 and 17 prepared in Comparative Examples 1 and 2 had high viscosity, the viscosity η1 after standing was measured using a viscosity / viscoelasticity measuring device ("HAAKE Rheo Stress 6000" manufactured by Thermo Scientific) at 25°C and 2 rpm.
[0152] The viscosity increase rate (η1 / η0) was calculated by dividing the viscosity after standing by the initial viscosity η1. The viscosity increase rate was evaluated according to the following criteria. The closer the viscosity increase rate is to 100%, the better. "0": Viscosity increase rate is less than 200% “×”: The weight reduction rate is 200% or more.
[0153] <Production of Cured Product of Resin Composition> A silicon tube was placed as a spacer on an aluminum plate coated with a release agent. Another aluminum plate coated with a release agent was placed on the silicon tube to form a gap between the two aluminum plates. Thus, a cast plate having a gap of 1 mm in thickness formed between the two aluminum plates was obtained. Resin compositions 1 to 18 were injected into the gap of the cast plate using a syringe, respectively, and thermally cured at 100° C. for 5 hours to obtain a cured product.
[0154] <Measurement of glass transition temperature> The obtained cured product was measured for glass transition temperature Tg using a viscoelasticity measuring apparatus ("DMA7100" manufactured by Hitachi, Ltd.) under tensile conditions (strain amplitude 10 μm, minimum tension 0 mN, tension gain 1.5, initial value of force amplitude 10 mN, 1 Hz) and evaluated according to the following criteria. "◎": Tg is 170℃ or higher "○": Tg is 150°C or higher and lower than 170°C “×”: Tg is lower than 150°C.
[0155] <Measurement of average linear thermal expansion coefficient (CTEα1 and CTEα2)> The cured product was cut to obtain a test piece with a width of 0.8 mm and a length of 15 mm. For the test piece, a thermomechanical analysis was performed by a tensile load method using a thermomechanical analyzer ("TMA7100" manufactured by Hitachi High-Technologies Co., Ltd.). Specifically, after the test piece was loaded into the device, it was measured twice continuously under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. The average linear thermal expansion coefficient (CTEα1: ppm / °C) in the first measurement range from 40°C to 60°C in the second measurement and the average linear thermal expansion coefficient (CTEα2: ppm / °C) in the second measurement range from Tg+40°C to 260°C were calculated and evaluated according to the following standards.
[0156] Evaluation criteria for the average linear thermal expansion coefficient CTEα1 within the first measurement range: “◎”: Average linear thermal expansion coefficient CTEα1 is less than 20ppm / ℃ “0”: The average linear thermal expansion coefficient CTEα1 is 20 ppm / °C or more and less than 50 ppm / °C “×”: The average linear thermal expansion coefficient CTEα1 is 50 ppm / °C or more.
[0157] Evaluation criteria for the average linear thermal expansion coefficient CTEα2 within the second measurement range: “◎”: Average linear thermal expansion coefficient CTEα2 is less than 50ppm / ℃ "0": The average linear thermal expansion coefficient CTEα2 is 50 ppm / °C or more and less than 100 ppm / °C “×”: The average linear thermal expansion coefficient CTEα2 is 100 ppm / °C or more.
[0158] <Results> The results of the above-mentioned examples and comparative examples are shown in the following table. In the following table, the meanings of the abbreviations are as follows. It should be noted that the viscosity of each material was measured by maintaining the temperature at 25°C ± 2°C using a vibration viscometer ("VM-10A-L" manufactured by Seconico Co., Ltd.). In addition, the numerical value in the column "(C) Viscosity" of the following table represents the viscosity of the highest viscosity among the (C) ethylenically unsaturated compounds used.
[0159] (A) Epoxy resin: “ZX-1059”: manufactured by Nippon Steel Chemical Materials Co., Ltd., a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, an epoxy resin that is liquid at 25°C, has 2 epoxy groups in one molecule, a viscosity of 2130 mPa·s, and an epoxy equivalent of 160 g / eq. to 170 g / eq.; “JER-604”: manufactured by Mitsubishi Chemical Corporation, a glycidylamine-type epoxy resin, an epoxy resin that is liquid at 25°C, has 4 epoxy groups in one molecule, a viscosity of 8000 mPa·s, and an epoxy equivalent of 110 g / eq. to 130 g / eq.; “HP-4032SS”: manufactured by DIC Corporation, a naphthalene-based epoxy resin, an epoxy resin that is liquid at 25°C, has two epoxy groups in one molecule, a viscosity of 39780 mPa·s, and an epoxy equivalent of 136 g / eq. to 148 g / eq.; “630”: manufactured by Mitsubishi Chemical Corporation, a glycidylamine-type epoxy resin that is liquid at 25°C, has 3 epoxy groups in one molecule, a viscosity of 980 mPa·s, and an epoxy equivalent of 90 g / eq. to 105 g / eq.
[0160] (B) Methacrylic Anhydride: “Methacrylic anhydride”: manufactured by Tokyo Chemical Industry Co., Ltd., anhydride group equivalent weight: 154 g / eq.
[0161] (C) Ethylenically unsaturated compounds: “GMA”: glycidyl methacrylate, manufactured by Mitsubishi Gas Chemical Co., Ltd., epoxy equivalent 142 g / eq., viscosity 2.0 mPa·s; “NPG”: neopentyl glycol dimethacrylate, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., viscosity 5.0 mPa·s; “PHE-1G”: phenoxyethylene glycol methacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., viscosity: 7.0 mPa·s.
[0162] (D) Epoxy polymerization accelerator: “2E4MZ”: organic base, 2-ethyl-4-methylimidazole, manufactured by Shikoku Chemicals Co., Ltd.
[0163] (E) Free Radical Polymerization Initiator: "PERHEXYL O": a free radical polymerization initiator, manufactured by NOF Corporation.
[0164] (F) Inorganic filling materials “Inorganic filler 1”: silica particles with an average particle size of 8 μm and a maximum particle size of 25 μm.
[0165] (G) Organic filling materials: “KMP-600”: silicone composite powder, average particle size 5 μm, manufactured by Shin-Etsu Silicone Co., Ltd.
[0166] (H) Optional additives: “HN-2200”: 3 or 4-methyl-1,2,3,6-tetrahydrophthalic anhydride (anhydride curing agent), manufactured by Showa Denko Materials Co., Ltd., anhydride equivalent: 166 g / eq.
[0167] (I) Organic solvent: 2-butanone.
[0168] [Table 1] [Table 1. Composition and results of Examples 1 to 9]
[0169] [Table 2] [Table 2. Compositions and results of Examples 10 to 15 and Comparative Examples 1 to 3]
[0170] Explanation of symbols 1, 100, 200, 300, 400, 500 Semiconductor chip packaging 10, 11, 12, 13, 14, 15 base plate 20, 21, 22, 23a, 23b, 24a, 24b, 25a, 25b Cured product of resin composition 30, 31, 32, 33, 34, 35 Semiconductor chips 36 Chip stack 37 Silicon perforated column 41, 42, 43, 44, 45, 46, 47, 48, 49 convex points 51 Sealing layer 61 Rewiring Layer 71, 72 through holes 80, 81 Silicon interposer.
Claims
1. A resin composition which is a liquid resin composition at 25°C, The resin composition comprises (A) an epoxy resin and (B) methacrylic anhydride, (A) The epoxy resin includes (A-1) an epoxy resin having two or more epoxy groups in one molecule and being liquid at 25°C.
2. The resin composition according to claim 1, wherein The amount of the component (A-1) is 10 to 100% by mass relative to 100% by mass of the component (A).
3. The resin composition according to claim 1, wherein The viscosity of the component (A-1) at 25°C is 100,000 mPa·s or less.
4. The resin composition according to claim 1, wherein The viscosity of the component (A) at 25° C. is 100,000 mPa·s or less.
5. The resin composition according to claim 1, wherein The mass ratio of the component (A) to the component (B) is 20 / 80 to 80 / 20.
6. The resin composition according to claim 1, wherein (C) A compound containing 1 to 3 ethylenically unsaturated bonds is further contained in addition to (B) component.
7. The resin composition according to claim 6, wherein The viscosity of the component (C) at 25°C is 30 mPa·s or less.
8. The resin composition according to claim 6, wherein The mass ratio of ((A) component + (B) component) / (C) component is 30 / 70 to 95 / 5.
9. The resin composition according to claim 1, wherein The composition further comprises (D) an epoxy polymerization accelerator.
10. The resin composition according to claim 1, wherein The composition further comprises (E) a radical polymerization initiator.
11. The resin composition according to claim 1, wherein The composition further comprises (F) an inorganic filler.
12. The resin composition according to claim 11, wherein The component (F) is silicon dioxide.
13. The resin composition according to claim 11, wherein The amount of the component (F) is 40 to 95% by mass based on 100% by mass of the nonvolatile matter in the resin composition.
14. The resin composition according to claim 11, wherein The viscosity of the resin composition at 25°C is 1000 mPa·s or less, The viscosity of the resin component of the resin composition at 25° C. is 30 mPa·s or less.
15. The resin composition according to claim 1, wherein It contains no organic solvent or contains less than 3% by mass of an organic solvent.
16. The resin composition according to claim 1, wherein When the resin composition is cured at 100° C. for 5 hours to obtain a cured product, The cured product has a glass transition temperature Tg of 220°C or less. The average linear thermal expansion coefficient CTEα1 of the cured product in the first measurement range of 40°C to 60°C is less than 50 ppm / °C, and the average linear thermal expansion coefficient CTEα2 of the cured product in the second measurement range of Tg+40°C to 260°C is less than 100 ppm / °C.
17. The resin composition according to claim 1, wherein When the resin composition is cured at 100° C. for 5 hours to obtain a cured product, The cured product has a glass transition temperature Tg of 150° C. or higher.
18. The resin composition according to claim 6, wherein (C) Component contains glycidyl methacrylate or 4-hydroxybutyl acrylate glycidyl ether. The resin composition according to claim 1 , which is an underfill material.
20. A semiconductor chip package, wherein: A cured product comprising the resin composition according to any one of claims 1 to 19.
21. The semiconductor chip package according to claim 20, wherein: The invention comprises: a substrate, a semiconductor chip provided on the substrate with a gap therebetween, and the cured product filling the gap.
22. A semiconductor device, wherein: A semiconductor chip package according to claim 20.
23. A cured product of the resin composition according to any one of claims 1 to 19.
Citation Information
Patent Citations
Transpirable repellent
JP1988040762B2
Liquid epoxy resin composition, cured product, method for manufacturing the same and resin composition for printed wiring board
JP2010070605A